Big Data for Small-scale Fisheries - Peskas in Timor-Leste - Palmer, Neil; Tilley, Alexander; Sozinho, Villiam (WorldFish, 2025)
Small-scale coastal fisheries in Timor-Leste (East Timor) are a vital source of food and income for thousands of people. But the lack of data on where fishers go and how much they catch has made it challenging for the government to develop policies to support and sustain the sector. Enter Peskas, a groundbreaking digital catch monitoring system developed by WorldFish with support from the Royal Norwegian Embassy in Jakarta, Pelagic Data Systems, and the CGIAR Initiative on Aquatic Foods. Peskas captures and shares critical fish catch data that enables smarter decision-making, and more sustainable management of coastal fisheries. In this short film you’ll learn all about how the innovation works, set in the stunning surroundings of Timor-Leste. Peskas is now being scaled up to four African countries with the support of UK International Development. Shot and produced by Neil Palmer for WorldFish.